2008
DOI: 10.1021/tx700341n
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-Modulated Mechanisms of the Cytotoxicity of Thimerosal and Inhibition of DNA Topoisomerase IIα

Abstract: Thimerosal is an organic mercury compound that is widely used as a preservative in vaccines and other solution formulations. The use of thimerosal has caused concern about its ability to cause neurological abnormalities due to mercury accumulation during a normal schedule of childhood vaccinations. While the chemistry and the biological effects of methylmercury have been well-studied, those of thimerosal have not. Thimerosal reacted rapidly with cysteine, GSH, human serum albumin, and single-stranded DNA to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 39 publications
3
35
1
3
Order By: Relevance
“…Thimerosal rapidly reacted with cysteine and GSH to form etHg-cysteine and etHg-GSH adducts in human leukemia K562 cells (Wu et al 2008). Thimerosal depleted intracellular GSH levels in these cells by 71% which markedly inhibited cell growth, corroborating a previous study using glioblastoma cells (James et al 2005).…”
Section: Intracellular Thiol Metabolism and Oxidative Imbalancesupporting
confidence: 84%
“…Thimerosal rapidly reacted with cysteine and GSH to form etHg-cysteine and etHg-GSH adducts in human leukemia K562 cells (Wu et al 2008). Thimerosal depleted intracellular GSH levels in these cells by 71% which markedly inhibited cell growth, corroborating a previous study using glioblastoma cells (James et al 2005).…”
Section: Intracellular Thiol Metabolism and Oxidative Imbalancesupporting
confidence: 84%
“…In addition, TM quickly reacts with other thiols forming Et-Hg adducts, reducing the availability of thiols in the cell [59]. Studies have shown that TM and other forms of Hg decrease the levels of total cellular thiols in general [60,61].…”
Section: Research Evidencementioning
confidence: 99%
“…However, previous studies demonstrated that hsTop2␣ is sensitive to thiol-reacting reagents and that cysteine modifications participate in a number of unique reactions (38 -41). For instance, thimerosal, a mercury-containing compound that rapidly reacts with thiol group, inhibited the topoisomerase II-decatenating activity (39). Thiopurines also inhibited topoisomerase II ATPase activity by alkylating thiol groups of cysteines (40).…”
Section: Discussionmentioning
confidence: 99%